Training Needs Analysis for the Level II National Leadership Training (PKN) to Enhance Strategic Leadership Competence (A Case Study at the Ministry of Finance) - Egrita Buntara (Journal of Creative Power and Ambition (JCPA), 2026)
Bureaucratic transformation, the strengthening of the merit system, and the implementation of talent management require Junior High-Level Leadership Officials (JPT Pratama) to possess strategic leadership competencies capable of anticipating change and navigating organizational complexity. However, the low proportion of JPT Pratama officials who have completed the Level II National Leadership Training (PKN Tingkat II) indicates that leadership competency development has not yet been optimized to meet organizational needs. This study aims to analyze the necessity of conducting PKN Tingkat II to enhance strategic leadership competencies within the Ministry of Finance, as well as its implications for strengthening the merit system, talent management, and succession planning. A qualitative approach with a case study design was employed, utilizing document analysis, observation, in-depth interviews, and Focus Group Discussions (FGDs); the data were analyzed thematically based on theories of Training Needs Analysis and strategic leadership. The findings reveal that the need for PKN Tingkat II is driven by organizational, job-related, and individual requirements. Furthermore, the program contributes to enhancing strategic leadership competencies—specifically in leading change, strategic decision-making, cross-organizational collaboration, coaching and mentoring, and professional networking. The study also demonstrates that PKN Tingkat II constitutes a strategic organizational necessity that supports the implementation of the merit system, talent management, and succession planning. Consequently, PKN Tingkat II should be positioned as a strategic organizational investment integrated with talent development to ensure the continuity of professional, adaptive, and competitive bureaucratic leadership.